MOGOK KERJA YANG MENGAKIBATKAN PEMUTUSAN HUBUNGAN KERJA (PHK) MASSAL PADA HOTEL PATRA JASA BALI - Sudirja S., Pande; Markeling, I Ketut; Pujawan, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
A strike is a fundamental right afforded to laborers and labor unions. A strike can not be done freely, there are limits and conditions that arrange. However, in some cases, still often strike that does not comply with the provisions of these regulations that could cause harm to employers and laborers themselves. This paper will describe the case of a strike occurred at Patra Jasa Hotel Bali, which resulted in Termination of Employment to 243 employees, this paper also describes the completion of the rights of employees who are experiencing Termination of Employment at Patra Jasa Hotel Bali under Act Number 13 Year 2003 about employment.
Keywords: Strike, Termination of Employment